Intermodal chassis supply in the US — A Bayesian game model. (March 2015) - Hartman, Bruce C.; Clott, Christopher
Abstract: A container requires a chassis for every over the road move. In North America, unlike Europe, approximately 30% of chassis have been owned by ocean carriers, who are divesting their chassis. Older chassis bring higher risk for damage or disruption on a trip, though they cost much less than new chassis. Who will provide chassis to facilitate container moves by truck for the growing amount of intermodal traffic flowing through the US? The issue is important for successful port operation, and may require at least operational improvements, and governance decisions by ports or terminal operators. We examine strategic possibilities for a trucker and shipper supplying chassis, using a Bayesian game. We find equilibrium and estimate typical values of decision parameters to make predictions about the signals shippers will send and corresponding truckers' strategy. Making truckers supply chassis may not be practical in North America, so additional specific policies and practices are needed. Inducing truckers to supply chassis under present economic conditions may require capital subsidies or higher freight costs, as well as improved operations.